Efektivitas Pengolahan Limbah Grey Water Melalui Ecotech Garden Skala Rumah Tangga di Kota Kupang - Elsa Maria Auxiliadora Lekipera da Costa; Marylin Susanti Junias; Mustakim Sahdan (Media Kesehatan Masyarakat, 2022)
In Kupang City, greywater is disposed of in the environment without any treatment, so it often causes problems in terms of aesthetics, health and exceeds the specified parameter limits. This study aims to determine the effectiveness of the Ecotech garden as one of the methods to treat greywater waste using water ornamental plants. This research type is quasi-experimental with a Group Pretest Posttest Design. The research sample is greywater from the inlet and outlet to be tested in the laboratory. Data were analyzed using the One Way Anova test with a p-value of 0.05, and the quality of wastewater before and after processing would be calculated using the effectiveness formula. Based on the analysis, it was found that the p-value of the three plants was 0,368 and shows that there is no significant difference between the three plants so that one of them can be selected. Based on the effectiveness value, Ecotech garden is considered very effective to reduce the greywater parameters concentration, namely BOD, COD, and TSS by 99% and 97%, while the concentration of ammonia (NH3) and pH both before and after processing are still below the quality standards. The most effective plants are the cattail plants and water hyacinth. It is suggested that Ecotech Garden can be maximally made on a communal scale, such as for housing and boarding houses/ dormitories by using several types of plants to be more effective in treating grey water waste.